Antibacterial Activity of Endophytic Actinobacteria Isolated from Ziziphus mauritiana Against Multidrug-Resistant Strains - Khairani, Hafifatunil; Priyanto, Jepri Agung; Prastya, Muhammad Eka; Retnowati, Dwi (UI Scholars Hub, 2025)
Increasing resistance to existing antibiotics has led to a need for new alternative sources. Among the possibilities that need to be explored is the endophytic actinobacteria associated with Ziziphus mauritiana. The present study aimed to evaluate the antibacterial activity of endophytic actinobacteria isolated from Z. mauritiana against five multidrug-resistant bacterial strains. Thirty actinobacteria isolates were obtained from the roots, stem, and leaves of the plant using the serial dilution technique. Using a double-layer agar test, we found that colonies from five of the 30 isolates (16%) exhibited antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) and the M18 strain of Bacillus subtilis. Interestingly, the crude extracts derived from four selected isolates (BBK 1, DBK 2, DBK 3, and DBSB 1) showed inhibitory activity against MRSA, with inhibition zone diameters ranging from 8 (±0.8) to 11 (±2.9) mm. The highest inhibition zone was seen in DBK 2. This had a zone diameter of 11 (±2.9) mm, which is not signifi-cantly different from the zone diameter of 12 (±0) mm seen in tetracycline. The minimum inhibitory concentrations (MICs) were determined using the micro-broth dilution technique. This showed MICs ranging from 2,500–5,000 μg/mL in the four extracts. Based on 16S ribosomal ribonucleic acid (rRNA) sequences, the four selected isolates were found to belong to the Streptomyces spp., with similarity values exceeding 99%. These four isolates require further study as potential antibiotic sources, particularly against MRSA.